On the fixed point principles of Banach and Kannan's - Leboukh, Somia (UNIVERSITE MOHAMED BOUDIAF - M’SILA FACULTE DES MATHEMATIQUES ET DE L’INFORMATIQUE, 2019)
Fixed-point theorems are very important tools in functional analysis, in this memory we study the different between the Banach and Kannan's principle in two cases metric spaces and functional spaces.
Keywords: Fixed point, metric space, Banach space, contraction…